4. CHARACTERISTICS OF THE DISEASE PATTERN AT LE VAN THINH HOSPITAL IN THE PERIOD OF 2018-2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This study aims to describe disease patterns at Le Van Thinh Hospital (LVTH) from 2018 to 2023.Methods: A cross-sectional descriptive study was conducted using retrospective data collection on patients with health insurance treated at LVTH from 2018 to 2023. Disease patterns were classified according to ICD-10 codes, treatment type (inpatient and outpatient), age group, and gender.Results: From 2018 to 2023, there were 2,716,943 patient visits with health insurance at LVTH. Pediatric patients constituted 10.1% of these visits, while female patients represented 58.6%. Outpatient visits consistently exceeded 95% of all treatments annually. The total number of inpatient and outpatient visits was lowest in 2021 but showed an increasing trend in 2022-2023. The three disease groups with the highest proportion of medical consultations and treatments are cardiovascular diseases (27.5%), respiratory diseases (12.5%), and endocrine, nutritional, and metabolic diseases (11.9%). Over the study period, 52.2% of total visits concentrated on ten main diseases, with essential primary hypertension accounting for 24.8% and type 2 diabetes for 9.3%. Among children, the most frequent diseases treated were acute rhinitis, acute pharyngitis, and acute tonsillitis. The disease groups with the highest number of treatments in both outpatient and inpatient settings (respiratory diseases, cardiovascular diseases, and gastrointestinal diseases) had the lowest number of treatments in 2021 during the entire period. The number of treatments decreased gradually from 2018 to 2021 and increased again in 2022- 2023, with 2023 recording the highest total number of treatments for the entire period.Conclusion: The study provides a comprehensive overview of common diseases and the changing trends in morbidity across the entire hospital. It includes both inpatient and outpatient treatments, and covers various age groups including children, adults, and the elderly. These findings offer a scientific basis for LVTH to adjust its drug list structure, develop more effective healthcare strategies, allocate resources reasonably, and enhance the quality of medical services for the regional population.
Keywords: Disease patterns, disease trends, Le Van Thinh Hospital, Covid-19